The spinning heart - Ryan, Donal 1977- (Black Swan Ireland, 2019)
Contemporary fiction. My father still lives back the road past the weir in the cottage I was reared in. I go there every day to see is he dead and every day he lets me down. He hasn't yet missed a day of letting me down. In the aftermath of Ireland's financial collapse, dangerous tensions surface in an Irish town. As violence flares, the characters face a battle between public persona and inner desires. Through a chorus of unique voices, each struggling to tell their own kind of truth, a single authentic tale unfolds. The Spinning Heart speaks for contemporary Ireland like no other novel. Wry, vulnerable, all-too human, it captures the language and spirit of rural Ireland and with uncanny perception articulates the words and thoughts of a generation. Technically daring and evocative of Patrick McCabe and J.M. Synge, this novel of small-town life is witty, dark and sweetly poignant. Donal Ryan's brilliantly realized debut announces a stunning new voice in literary fiction
Keywords: Villages / Ireland / Fiction; Interpersonal relations / Fiction; Ireland / Fiction; Ireland / Social conditions / 21st century / Fiction; Interpersonal relations; Social conditions; Villages; Ireland; 2000-2099; Fiction